Selection of Elite Lines in Triple Cross F1 Population of Tomato (Solanum lycopersicum L.) through Principal Component Analysis - Reddy, P. S. K.; Reddy, P. S. S.; Yerasu, S. R.; Tiwari, J. K.; Syed, Sadarunnisa; Sireesha, Y. (International Journal of Bio-resource and Stress Management, 2026)
The study was conducted during August, 2024–February, 2025 at the ICAR-Indian Institute of Vegetable Research, Varanasi, Uttar Pradesh, India to select superior lines from early segregating population. Principal component analysis was conducted to identify major contributing agro-horticultural traits and superior lines in a selected triple cross tomato population. Tomato, one of the most important vegetable crops worldwide due to its high economic value, nutritional significance and wide adaptability. The scree plot revealed that the first five principal components (PCs) accounted for 86.7% of the total variability, with PC1 and PC2 explaining 36.7% and 20.6%, respectively. Together, these two components captured 57.3% of the overall variation, indicating their effectiveness in summarizing population diversity. The biplot and loading matrix demonstrated that fruit length, fruit diameter, fruit weight and pericarp thickness exhibited strong positive loadings on PC1, identifying it as the primary yield and fruit size axis. Total soluble solids and number of locules showed moderate positive association with PC1 and strong loading on PC5 (0.770), indicating partial independence of fruit quality traits from yield components. Genotypic distribution in the biplot identified TCH-55, TCH-125 and TCH-57 as superior for yield attributes, while TCH-13 and TCH-7 were promising for quality improvement. The clear separation of yield, vegetative, and quality traits across principal components highlighted the multidimensional variability generated through triple cross breeding and provided a strategic framework for simultaneous selection of high-yielding and quality genotypes.